Quality assessment of stored fresh Cassava Roots and 'fufu' flour produced from stored roots - Omosuli SV; Ikujenlola AV; Abisuwa AT (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2017)
The aim of this study was to assess the quality characteristics of cassava roots and fermented cassava    flour (fufu). Matured cassava was carefully uprooted and stored in high density polyethylene bag for a period ranging from 0 to 10 days. Fermented cassava fl our was produced using standard methods. The stored roots were assessed for various quality properties like percentage loss, discoloration, peel to pulp ratio. Also physico-chemical and sensory of 'fufu' fl our produced from stored roots were assessed using standard methods. There was found a decrease in the percentage pulp obtained and a corresponding increase in the percentage peel from 22.10% to 35.90% as the period of storage progressed. The  moisture and starch contents decreased while the ash, crude-fibre and sugar contents increased during the study. The yield of 'fufu' fl our and cyanogenic potential decreased as the storage period progressed. There was no significant difference among 'fufu' samples produced from roots stored for the fi rst seven days with respect to sensory qualities. The study shows that cassava roots can be stored effectively in high density polyethylene bag and result in acceptable product.